Socioeconomic, clinical and pharmacotherapy profile of geriatric patients with Diabetes Mellitus (Research, Society and Development, 2021)
In Brazil, there are studies that prove how much the epidemiological conditions of chronic diseases, such as diabetes mellitus, are growing more and more, directly affecting geriatric patients. The present study aimed to analyze the socioeconomic and clinical profile, as well as the pharmacotherapy of geriatric patients with diabetes mellitus. This is a descriptive and quantitative research, in which variables related to the socioeconomic, clinical and therapeutic profile of elderly patients were analyzed. The data were represented using tables and statistical analysis. The results showed that grade 1 obesity occurred more frequently in the elderly who receive 1 to 2 minimum wages, with type 2 diabetes and females. It was observed that in overweight patients, type 2 diabetes also prevailed, but there was a predominance of males. It should be noted that almost entirely, the elderly declared an absence of physical activity. The most widely used oral medication was Metformin and the injectables were NPH insulin, followed by regular insulin. Regarding tests for glycemic control, it was found that this is usually done annually.